THE IMPLEMENTATION OF WAQF ISTIBDAL IN WAQF MUSHOLA (CASE STUDY OF THE CONSTRUCTION OF GEMPOL-PASURUAN TOLL ROAD SECTION I AND II) - Yoga Rizki Prihanto; Siti Inayatul Faizah (Universitas Airlangga, 2020)
The background of this research is the existence of massive infrastructure development by the government, one of which is the construction of the Gempol-Pasuruan Toll Road. The construction process of the Gempol-Pasuruan Toll Road passes through the land and buildings owned by residents and including to waqf land. One of the waqf land affected by the construction process of the Gempol-Pasuruan Toll Road is the Al-Mukmin Mosque. This phenomenon encourages researchers to conduct research that discusses how the waqf istibdal process, both in terms of changes in waqf assets and in the administration process of licensing. This study uses a qualitative approach with a case study strategy. Data is collected through interviews with relevant parties and documentation of related documents. The results of this study indicate that the process of changing the waqf assets of the Al-Mukmin Mosque is in accordance with statutory procedures. The waqf istibdal process consists of the process of changing the waqf property and the administrative licensing process. The process of changing waqf property consists of planning, implementation, coordination between toll management and nazir, searching for replacement land, replacing land replacement processes, and the process of building a new mosque. The second process consists of a licensing process that starts from nazir, the Office of the Ministry of Religion Pasuruan Regency, and the Regional Office of the Ministry of Religion of East Java.Keywords: waqf, waqf istibdal, mosque, Gempol-Pasuruan Toll RoadREFFERENCEDirektorat Pemberdayaan Wakaf Direktorat Jenderal Bimbingan Masyarakat Islam Departemen Agama. Fiqih wakaf. Jakarta: Departemen Agama.Direktorat Pemberdayaan Wakaf. (2007). Paradigma baru wakaf di Indonesia. Cet 1. Jakarta: Dirjen Bimas Islam.Direktorat Pengembangan Zakat dan Wakaf. (2005). Wakaf tunai dalam perspektif hukum Islam. Jakarta: TP.Halim, Abdul. M.A. (2005). Hukum perwakafan di Indonesia. Jakarta: Ciputat Press. Kahf, Monzer. (2006). al-Waqf al-Islami taṣawwuruhu, idaratuhu, tanmiyatuhu. Damaskus: Dar al-Fikr.Karim, Shamsiah Bte Abdul. (2010). Contemporary of shari’a compliance structuring for the development and management of waqf asset in Singapore. Kyoto Bulletin of Islamic Area Studies, 3(2), 143–164. Mugniyah, Muhammad Jawad. (2010). Fiqh lima madzhab: Ja’fari, hanafi, syafi’i, hambali. Jakarta: Lentera.Mukhlisin, Muzarie. (2010). Hukum perwakafan dan implikasinya terhadap kesejateraan umat (implementasi wakaf di pondok modern darussalam gontor). cet 1. Jakarta: Kementerian Agama.Peraturan Pemerintah Nomor 42 Tahun 2006 tentang Pelaksanaan Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf dan Kompilasi Hukum Islam.Peraturan Pemerintah Republik Indonesia No. 8 Tahun 1990 Tentang Jalan Tol.Peraturan Pemerintah Republik Indonesia Nomor 25 Tahun 2018 tentang Perubahan Atas Peraturan Pemerintah Nomor 42 Tahun 2006 Tentang Pelaksanaan Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf Dalam Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf.Sugiyono. (2012). Metode penelitian kuantitatif kualitatif dan R&D. Bandung: Alfabeta.Undang-Undang Nomor 26 Tahun 2007 Tentang Penataan Ruang.Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf.Wirartha, I Made. (2006). Metodologi penetilian sosial ekonomi. Yogyakarta: CV Andi Offset.Yin, Robert. K. (2009). Studi kasus; Desain dan metode. Jakarta: Raja Grafindo Persada.bpjt.pu.go.id/ (laman Badan Pengatur Jalan Tol)www.jasamarga.com (laman Jasa Marga)https://bwi.or.id/ (laman Badan Wakaf Indonesia)